Bardzo proszę o pomoc
Rozwiąż równanie: (2x-1)² -3x² = 6(x-4)


Odpowiedź :

Odpowiedź:

[tex]\huge\boxed{\boxed{x=5}}[/tex]

Szczegółowe wyjaśnienie:

Rozwiązanie równania

[tex](2x-1)^2-3x^2=6(x-4)\\\\(2x)^2-2\cdot2x\cdot1+1^2-3x^2=6x-24\\\\4x^2-4x+1-3x^2-6x+24=0\\\\x^2-10x+25=0\\\\a=1, \ b=-10, \ c=25\\\\\Delta=b^2-4ac\Rightarrow(-10)^2-4\cdot1\cdot25=100-100=0\\\\\Delta=0\Leftarrow jedno \ rozwiazanie\\\\x=\frac{-b}{2a}=\frac{-(-10)}{2\cdot1}=\frac{10}{2}=5[/tex]

Wykorzystano wzór skróconego mnożenia

  • na kwadrat różnicy

[tex](a-b)^2=a^2-2ab+b^2[/tex]